3-(2-Fluorophenyl)-6-(phenoxymethyl)-1,2,4-triazolo[3,4-b][1,3,4]thiadiazole - Holm, Melanie (International Union of Crystallography, 2008)
The crystal structure of the title compound, C(16)H(11)FN(4)OS, was synthesized in the course of our studies on 1,2,4-triazolo[3,4-b][1,3,4]thiadiazoles as inhibitors of p38 mitogen-activated protein kinase (MAPK). The three-dimensional data obtained were used to generate a three-dimensional pharmacophore model for in silico database screening. The dihedral angles between the central heterocylic system and the fluorophenyl and phenyl rings are 20.21 (3) and 5.43 (1)°, respectively; the dihedral angle between the two benzene rings is 15.80 (4)°.